Pengaruh Informasi Kinerja Saham terhadap Pengambilan Keputusan Investasi dengan Herding Behavior sebagai Variabel Mediasi - Winda Wulan Sari; Ahmad Fauzan Fathoni; Haryetti Haryetti (Jurnal Ekonomi, 2019)
Investor often behave irrationally on investment decision making. Herding behavior is believed to occur in the capital market. This study aims to determine the effect of stock performance information on investment decision making with herding behavior as a mediating variable for investors who open securities accounts through the Investment Gallery at the University of Riau. The population in this study included all respondents' answers to the questionnaire that had been distributed through the google form. Primary data is collected by questionnaire as an instrument to prove the results of research, to test the hypothesis in this study is to use path analysis. The sampling technique that has been chosen is an incidental method that is giving the opportunity to the entire population to be sampled but will be re-elected according to the characteristics desired by the author (142 investors who invest more than 1 year). The results obtained showed that, First of all, information of stock performance has an effect on herding behavior. Secondly, information of stock performance influences investment decision making. Thirdly, herding behavior influences investment decision making. Finally, herding behavior is able to mediate the influence information of stock performance on investment decision making. The findings of this study were investors have an information but they still behave irrational as herding behavior on investment decision making.